Attainable measures for certain types of $p$-adic Duffin-Schaeffer sets - Laursen, Mathias L. (MATHEMATICA SCANDINAVICA, 2023)
This paper settles recent conjectures concerning the $p$-adic Haar measure applied to a family of sets defined in terms of Diophantine approximation. This is done by determining the spectrum of measure values for each family and seeing that this contradicts the corresponding conjectures.